Continuous Metabolic Monitoring in Infant Cardiac Surgery: Toward an Individualized Cardiopulmonary Bypass Strategy. Issue 1 (19th November 2015) - Torre, Salvatore; Biondani, Elisa; Menon, Tiziano; Marchi, Diego; Franzoi, Mauro; Ferrarini, Daniele; Tabbì, Rocco; Hoxha, Stiljan; Barozzi, Luca; Faggian, Giuseppe; Luciani, Giovanni Battista
Abstract: Cardiopulmonary bypass (CPB) in infants is associated with morbidity due to systemic inflammatory response syndrome (SIRS). Strategies to mitigate SIRS include management of perfusion temperature, hemodilution, circuit miniaturization, and biocompatibility. Traditionally, perfusion parameters have been based on body weight. However, intraoperative monitoring of systemic and cerebral metabolic parameters suggest that often, nominal CPB flows may be overestimated. The aim of the study was to assess the safety and efficacy of continuous metabolic monitoring to manage CPB in infants during open‐heart repair. Between December 2013 and October 2014, 31 consecutive neonates, infants, and young children undergoing surgery using normothermic CPB were enrolled. There were 18 male and 13 female infants, aged 1.4 ± 1.7 years, with a mean body weight of 7.8 ± 3.8 kg and body surface area of 0.39 m 2 . The study was divided into two phases: (i) safety assessment; the first 20 patients were managed according to conventional CPB flows (150 mL/min/kg), except for a 20‐min test during which CPB was adjusted to the minimum flow to maintain MVO2 >70% and rSO2 >45% (group A); (ii) efficacy assessment; the following 11 patients were exclusively managed adjusting flows to maintain MVO2 >70% and rSO2 >45% for the entire duration of CPB (group B). Hemodynamic, metabolic, and clinical variables were compared within and between patient groups. Demographic variables were comparable in the two groups. In group A, the 20‐min test allowed reduction of CPB flows greater than 10%, with no impact on pH, blood gas exchange, and lactate. In group B, metabolic monitoring resulted in no significant variation of endpoint parameters, when compared with group A patients (standard CPB), except for a 10% reduction of nominal flows. There was no mortality and no neurologic morbidity in either group. Morbidity was comparable in the two groups, including: inotropic and/or mechanical circulatory support (8 vs. 1, group A vs. B, P = 0.07), reexploration for bleeding (1 vs. none, P = not significant [NS]), renal failure requiring dialysis (none vs. 1, P = NS), prolonged ventilation (9 vs. 4, P = NS), and sepsis (2 vs. 1, P = NS). The present study shows that normothermic CPB in neonates, infants, and young children can be safely managed exclusively by systemic and cerebral metabolic monitoring. This strategy allows reduction of at least 10% of predicted CPB flows under normothermia and may lay the ground for further tailoring of CPB parameters to individual patient needs.